Design of a multinational randomized controlled trial to assess the effects of structured and individualized exercise in patients with metastatic breast cancer on fatigue and quality of life: the EFFECT study - Hiensch, Anouk E.; Monninkhof, Evelyn M.; Schmidt, Martina; Zopf, Eva M.; Bolam, Kate A.; Aaronson, Neil K.; Belloso, Jon; Bloch, Wilhelm; Clauss, Dorothea; Depenbusch, Johanna; Lachowicz, Milena; Pelaez, Mireia; et al. (Trials, 2022)
Many patients with metastatic breast cancer experience cancer- and treatment-related side effects that impair activities of daily living and negatively affect the quality of life. There is a need for interventions that improve quality of life by alleviating fatigue and other side effects during palliative cancer treatment. Beneficial effects of exercise have been observed in the curative setting, but, to date, comparable evidence in patients with metastatic breast cancer is lacking. The aim of this study is to assess the effects of a structured and individualized 9-month exercise intervention in patients with metastatic breast cancer on quality of life, fatigue, and other cancer- and treatment-related side effects.